Micro-nano multi-level heterogeneous structure eutectic high-entropy alloy erosion-resistant coating and its preparation and application

CN122406221BActive Publication Date: 2026-10-09NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610878755.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-09
Estimated Expiration
2046-06-17

AI Technical Summary

Technical Problem

[0006]针对现有技术中耐磨性与耐蚀性难以兼顾及常规多相共晶高熵合金中局部成分起伏较大易诱发局部腐蚀等问题,本发明的主要目的在于提供一种微纳多级异质结构的共晶高熵合金耐磨蚀涂层及其制法与应用,所述涂层通过特定合金成分设计与非平衡快速凝固工艺相结合,在微米尺度形成FCC/BCC双相异质结构,并在BCC相域内部进一步形成由无序BCC相和有序B2相构成的纳米尺度成分调制结构,从而实现耐蚀性与耐磨性的协同提升,适用于海洋装备关键部件的表面防护

Benefits of technology

[0015] (1) This invention combines a specific Al-Co-Cr-Fe-Ni-Ti-Nb alloy composition design with a non-equilibrium rapid solidification process to construct a micron-scale FCC/BCC dual-phase heterostructure in a eutectic high-entropy alloy wear-resistant coating, and further forms a nano-scale BCC/B2 heterostructure within the BCC phase domain, thereby forming a micro-nano multi-level heterostructure. This structure is different from alloy coatings that only have conventional dual-phase eutectic structures. It can achieve microstructure control at different scales through low-cost microalloying and efficient cladding manufacturing processes, providing a structural basis for the synergistic improvement of corrosion resistance, wear resistance and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122406221B_ABST
    Figure CN122406221B_ABST
Patent Text Reader

Abstract

The application discloses a kind of micro-nano multistage heterogeneous structure eutectic high-entropy alloy erosion-resistant coating and its preparation method and application.The general formula of the chemical element composition of the eutectic high-entropy alloy erosion-resistant coating is Al a Co b Cr c Fe d Ni e Ti f Nb g , the eutectic high-entropy alloy erosion-resistant coating includes FCC phase and BCC phase area, the BCC phase area is distributed in the FCC phase as matrix, the BCC phase area forms nanometer scale component modulation area inside, the nanometer scale component modulation area is composed of disordered BCC phase and ordered B2 phase;The eutectic high-entropy alloy erosion-resistant coating has micron scale FCC / BCC dual-phase heterogeneous structure and nanometer scale BCC / B2 heterogeneous structure.The micro-nano multistage heterogeneous structure of the coating in the application is beneficial to improve the corrosion resistance and anti-wear-corrosion coupling damage capacity of the coating in seawater environment, and is suitable for the surface protection of key parts of marine equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface protection technology, specifically relating to a wear-resistant coating of a micro / nano multi-level heterostructure eutectic high-entropy alloy, its preparation method, and its application. Background Technology

[0002] Major marine engineering projects are placing increasingly stringent demands on the reliability and service life of key equipment components. In the complex marine environment, moving mechanical parts not only face severe seawater corrosion but also endure continuous mechanical wear; these two factors are coupled, significantly accelerating material damage and failure. This harsh condition of coexisting corrosion and wear poses a severe challenge to the surface protection capabilities of marine engineering structural components.

[0003] High-energy beam surface engineering techniques (such as laser cladding and plasma welding) are crucial for preparing metallurgically bonded alloy coatings, enhancing the surface properties and extending the service life of marine engineering structural components. However, traditional alloy coating materials (such as iron-based alloys) have inherent limitations in simultaneously achieving excellent corrosion resistance and wear resistance, making them unsuitable for the extreme marine environment. In recent years, high-entropy alloys, with their unique diversified composition design concept, have broken through the traditional alloy composition design framework dominated by single or small amounts of elements, becoming a new material system with great application potential. Among them, eutectic high-entropy alloys, especially those based on AlCoCrFeNi... 2.1 The alloy system represented by [specific alloy name] achieves a good balance between strength and plasticity by forming a layered two-phase structure with alternating face-centered cubic (FCC) and body-centered cubic (BCC) phases in situ during solidification.

[0004] However, existing research indicates that the multiphase structure of eutectic high-entropy alloys has a decisive influence on their corrosion behavior, with microgalvanic corrosion being one of the core issues. In chloride-rich marine environments, different phases within the alloy (such as the Cr-rich FCC phase and the Ni-Al-rich BCC phase) form microgalvanic coupling due to differences in electrode potential. This leads to selective dissolution of the more negatively potentialed BCC phase, thereby inducing the initiation and propagation of pitting corrosion. In typical AlCoCrFeNi alloys... 2.1 This problem is even more pronounced in eutectic high-entropy alloys. More critically, current research largely focuses on the behavior of materials under static corrosive environments, severely neglecting the coupling effect of corrosion and wear prevalent in marine conditions. Under dynamic conditions such as wave erosion, impact from suspended objects, and relative sliding of moving parts, the coating surface simultaneously suffers synergistic damage from electrochemical corrosion and mechanical wear. Corrosion accelerates the wear process (the fresh surface exposed after the corrosion product film peels off is more susceptible to wear), and wear also exacerbates corrosion damage (local damage to the passivation film triggers the rapid dissolution of fresh metal). Under such abrasive conditions, simply possessing excellent corrosion resistance or wear resistance is insufficient to guarantee the long-term effective service life of the coating.

[0005] Currently, no eutectic high-entropy alloy coating can effectively suppress pitting corrosion initiation and propagation and resist synergistic wear-corrosion damage from the microstructural design stage, specifically targeting marine abrasive environments. How to achieve toughening using a two-phase heterostructure while preventing it from becoming a source of corrosion and wear, or even enabling it to play a positive role in the abrasion process, remains a bottleneck that current technology has not yet overcome. Therefore, developing a novel eutectic high-entropy alloy coating material and its preparation method that can form a stable passivation film in a static corrosive environment to resist pitting corrosion initiation and propagation, and effectively suppress synergistic wear-corrosion damage under dynamic abrasive conditions, has become a key technical problem urgently needing to be solved in this field. Summary of the Invention

[0006] To address the challenges of simultaneously achieving wear resistance and corrosion resistance in existing technologies, as well as the large fluctuations in local composition in conventional multiphase eutectic high-entropy alloys that easily induce localized corrosion, the main objective of this invention is to provide a wear-resistant coating of a micro / nano-level heterostructure eutectic high-entropy alloy, its preparation method, and its application. This coating, through a combination of specific alloy composition design and a non-equilibrium rapid solidification process, forms an FCC / BCC dual-phase heterostructure at the micrometer scale. Furthermore, within the BCC phase domain, a nanoscale compositional modulation structure composed of disordered BCC phases and ordered B2 phases is formed, thereby achieving a synergistic improvement in both corrosion resistance and wear resistance. This coating is suitable for surface protection of key components in marine equipment.

[0007] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0008] This invention provides a wear-resistant coating of a eutectic high-entropy alloy with a micro / nano hierarchical heterostructure, wherein the general formula of the chemical element composition of the eutectic high-entropy alloy wear-resistant coating is Al. a Co b Cr c Fe d Ni e Ti f Nb g , among them, a=13~17 at.%, b=14~17 at.%, c=14~17 at.%, d=16~19 at.%, e=30~34 at.%, f=3~5 at.%, g=0~3at.%, a+f+g=16~22 at.%, a+b+c+d+e+f+g=100 at.%;

[0009] The eutectic high-entropy alloy wear-resistant coating includes an FCC phase and a BCC phase domain. The BCC phase domain is distributed within the FCC phase, which serves as the matrix. A nanoscale composition modulation region is formed within the BCC phase domain. The nanoscale composition modulation region is composed of a disordered BCC phase and an ordered B2 phase. The eutectic high-entropy alloy wear-resistant coating has a micron-scale FCC / BCC dual-phase heterostructure and a nanoscale BCC / B2 heterostructure.

[0010] This invention also provides a method for preparing the aforementioned wear-resistant coating of a eutectic high-entropy alloy with a micro / nano hierarchical heterostructure, comprising:

[0011] Provides substrates and multi-principal component powders;

[0012] Furthermore, the multi-principal element powder is clad onto the surface of a substrate using laser cladding technology, and then naturally cooled in air to obtain a wear-resistant coating of a eutectic high-entropy alloy with a micro-nano multi-level heterostructure.

[0013] This invention also provides the application of the aforementioned micro / nano hierarchical heterostructure eutectic high-entropy alloy wear-resistant coating in the surface protection of key components of marine equipment.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0015] (1) This invention combines a specific Al-Co-Cr-Fe-Ni-Ti-Nb alloy composition design with a non-equilibrium rapid solidification process to construct a micron-scale FCC / BCC dual-phase heterostructure in a eutectic high-entropy alloy wear-resistant coating, and further forms a nano-scale BCC / B2 heterostructure within the BCC phase domain, thereby forming a micro-nano multi-level heterostructure. This structure is different from alloy coatings that only have conventional dual-phase eutectic structures. It can achieve microstructure control at different scales through low-cost microalloying and efficient cladding manufacturing processes, providing a structural basis for the synergistic improvement of corrosion resistance, wear resistance and structural stability.

[0016] (2) The nanoscale composition modulation structure inside the BCC phase domain in this invention is beneficial to reduce the local composition fluctuation scale and improve the surface passivation behavior. Compared with coarse-scale composition partitioning, fine-scale heterostructure is beneficial to form a passivation film with more continuous distribution and more uniform composition under the action of corrosive media, reducing the tendency of local continuous dissolution, thereby improving the corrosion resistance of the coating in the seawater environment.

[0017] (3) The Al, Ti, Nb and Cr elements introduced in this invention work together to improve the stability of the passivation film and the repassivation ability after local film rupture. In the local corrosion area, a regenerated coating layer containing Al, Ti and Nb oxides can be generated in situ, and it works together with the passivation products in the Cr-rich area to effectively control the expansion of pitting corrosion.

[0018] (4) The micro-nano hierarchical heterostructure in this invention is beneficial to balance the load-bearing capacity, wear resistance and crack resistance of the coating; among them, the FCC continuous phase is beneficial to improve the toughness of the coating and alleviate local stress concentration, and the BCC / B2 related structure is beneficial to improve the hardness, plastic cutting resistance and micro-cutting wear resistance of the coating, thereby improving the structural stability and wear resistance of the coating under friction load.

[0019] (5) The coating in this invention is suitable for surface protection of key components of marine equipment, especially for service scenarios that face seawater corrosion, mechanical wear and wear-corrosion coupling effects at the same time; the preparation method is efficient and flexible, suitable for preparing coatings on the surface of complex-shaped parts, and has good engineering application prospects and promotion value. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a low-magnification TEM image of the wear-resistant coating of the micro / nano hierarchical heterostructure eutectic high-entropy alloy prepared in Example 1 of the present invention;

[0022] Figure 2 This is a STEM-EDS surface scan image of the BCC phase domain inside the wear-resistant coating of the micro / nano hierarchical heterostructure eutectic high-entropy alloy prepared in Example 1 of the present invention;

[0023] Figure 3 The graph shows the potentiodynamic polarization test results of the coatings prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 of this invention.

[0024] Figures 4a-4c The images shown are, respectively, a cross-sectional TEM image of the surface passivation film of the micro / nano hierarchical heterostructure eutectic high-entropy alloy wear-resistant coating prepared in Example 1 of the present invention, a STEM-EDS oxygen distribution surface scan result of the surface passivation film, and an XPS test result of the surface passivation film.

[0025] Figure 5 The images show the microhardness test results of the coatings prepared in Examples 1, 2, Comparative Example 1, and Comparative Example 2 of this invention.

[0026] Figures 6a-6b These are schematic diagrams of the average two-dimensional profile of the wear track cross-section and the three-dimensional morphology of the surface after abrasion testing of the coating prepared in Example 1 of the present invention in an artificial seawater environment.

[0027] Figures 6c-6d These are schematic diagrams of the average two-dimensional profile of the wear track cross-section and the three-dimensional morphology of the surface after the abrasion test of the coating prepared in Example 2 of the present invention in an artificial seawater environment.

[0028] Figures 6e-6f These are schematic diagrams of the average two-dimensional profile of the wear track cross section and the three-dimensional morphology of the surface after abrasion testing of the coating prepared in Comparative Example 1 of the present invention in an artificial seawater environment.

[0029] Figure 7 This is a TEM image of the near-surface cross-section region of the wear-resistant coating of the micro-nano hierarchical heterostructure eutectic high-entropy alloy prepared in Example 1 of the present invention after being subjected to wear test in an artificial seawater environment;

[0030] Figure 8 This is a SEM image of the coating prepared in Comparative Example 2 of the present invention;

[0031] Figure 9 This is a SEM image of the coating prepared in Comparative Example 3 of the present invention. Detailed Implementation

[0032] In view of the deficiencies of the prior art, the inventors of this case, through long-term research and extensive practice, have proposed the technical solution of this invention. The technical solution of this invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0033] Specifically, as one aspect of the technical solution of this invention, the general formula of the chemical element composition of the wear-resistant coating of a micro / nano hierarchical heterostructure eutectic high-entropy alloy is Al. a Co b Cr c Fe d Ni e Ti f Nb g , among them, a=13~17 at.%, b=14~17 at.%, c=14~17 at.%, d=16~19 at.%, e=30~34 at.%, f=3~5 at.%, g=0~3at.%, a+f+g=16~22 at.%, a+b+c+d+e+f+g=100 at.%;

[0034] The eutectic high-entropy alloy wear-resistant coating includes an FCC phase and a BCC phase domain. The BCC phase domain is distributed within the FCC phase, which serves as the matrix. A nanoscale composition modulation region is formed within the BCC phase domain. The nanoscale composition modulation region is composed of a disordered BCC phase and an ordered B2 phase. The eutectic high-entropy alloy wear-resistant coating has a micron-scale FCC / BCC dual-phase heterostructure and a nanoscale BCC / B2 heterostructure.

[0035] In some preferred embodiments, the elements in the coating are within the aforementioned composition range, and the coating composition is located near the eutectic composition region. This is beneficial for forming a biphase eutectic structure dominated by FCC and BCC phases under non-equilibrium rapid solidification conditions of laser cladding. Preferably, the FCC phase forms a continuous network phase, and the BCC phase domains are distributed within the FCC network structure, thereby forming a micron-scale FCC / BCC biphase heterostructure.

[0036] Furthermore, within the BCC phase domain, due to the combined effects of the alloy element distribution differences and the non-equilibrium rapid solidification of laser cladding, a nanoscale compositional modulation structure composed of disordered BCC phase and ordered B2 phase can be further formed, thereby introducing a nanoscale heterostructure within the micron-scale eutectic structure and forming a micro-nano hierarchical heterostructure.

[0037] The micro-nano hierarchical heterostructure improves the coating's load-bearing capacity, resistance to plastic cutting, and wear resistance through the high-density interface and coherent strain field provided by the nanoscale coherent amplitude modulation structure between the hard phase and the ordered phase. On the other hand, it alleviates local stress concentration and improves the coating's toughness and crack resistance through the FCC continuous phase. The multi-scale strain distribution between different regions and between multiple phases in this unique hierarchical heterostructure generates anomalous heterogeneous deformation-induced strengthening, which is beneficial to improving the structural stability of the coating under friction conditions.

[0038] In some preferred embodiments, the nanoscale component modulation region is formed by amplitude modulation decomposition, and the modulation period between the disordered BCC phase and the ordered B2 phase is 20 nm to 200 nm.

[0039] In some preferred embodiments, the phase interface between the disordered BCC phase and the ordered B2 phase in the nanoscale composition modulation region is coherent.

[0040] In some preferred embodiments, the disordered BCC phase and the ordered B2 phase in the nanoscale component modulation region are distributed in a continuously interwoven labyrinthine pattern.

[0041] Furthermore, the nanoscale composition modulation structure of the nanoscale composition modulation region reduces the scale of local compositional fluctuations within the BCC phase domain, which is beneficial for forming a more continuous and uniformly composed passivation film under the action of corrosive media. The passivation film may contain oxides of Cr, Al, Ti, Nb, Co, Fe, and Ni, which is beneficial for forming a dense amorphous passivation film. In particular, when the passivation film is locally damaged, the nanoscale composition modulation enables the passivation film to quickly replenish film-forming elements from the underlying B2 phase (rich in Al, Ti, and Nb) and BCC phase (rich in Cr) after local rupture, forming a regenerated capping layer containing Al, Ti, and Nb oxides in situ, achieving "intelligent" self-repair, thereby reducing the tendency for local continuous dissolution and effectively restraining the expansion of pitting corrosion pits. This is the fundamental reason for its high pitting potential.

[0042] In some preferred embodiments, the volume fraction of the FCC phase in the eutectic high-entropy alloy wear-resistant coating is 40% to 55%. Within this range, it is beneficial to balance the toughness and corrosion resistance provided by the FCC phase with the load-bearing capacity and wear resistance provided by the BCC / B2 related structure, thereby obtaining better overall wear-resistant performance.

[0043] In some preferred embodiments, the thickness of the eutectic high-entropy alloy wear-resistant coating is 0.5~1.5 mm.

[0044] In some preferred embodiments, the eutectic high-entropy alloy wear-resistant coating is an Al-Co-Cr-Fe-Ni-Ti-Nb system coating formed using non-equilibrium rapid solidification technology.

[0045] In some preferred embodiments, the eutectic high-entropy alloy wear-resistant coating forms a continuous passivation film on the surface in a simulated seawater environment, the passivation film containing oxides of Cr, Al, Ti, Nb, Co, Fe, and Ni.

[0046] Furthermore, the passivation film is continuously distributed on the surface of different phase regions and has the ability to be repassivated after local film rupture. The repassivation product contains one or more of Al, Ti, and Nb oxides.

[0047] In some preferred embodiments, the coating of the present invention exhibits excellent corrosion resistance and abrasion resistance in a simulated seawater environment, and the self-corrosion current density of the eutectic high-entropy alloy abrasion-resistant coating in a simulated seawater environment is ≤8.53×10⁻⁶. -8 A / cm -2 The passivation current density is ≤8.67×10⁻⁶. -7 A / cm -2 Its pitting potential relative to the silver / silver chloride electrode is ≥660mV.

[0048] In some preferred embodiments, the volumetric wear rate of the eutectic high-entropy alloy wear-resistant coating is ≤3×10⁻⁶ under simulated seawater conditions. -6 mm 3 / (N·m).

[0049] Furthermore, the simulated seawater environment is a 3.5 wt% sodium chloride aqueous solution.

[0050] Another aspect of this invention provides a method for preparing the aforementioned wear-resistant coating of a micro / nano hierarchical heterostructure eutectic high-entropy alloy, comprising:

[0051] Provides substrates and multi-principal component powders;

[0052] Furthermore, the multi-principal element powder is clad onto the surface of a substrate using laser cladding technology, and then naturally cooled in air to obtain a wear-resistant coating of a eutectic high-entropy alloy with a micro-nano multi-level heterostructure.

[0053] In some preferred embodiments, the multi-principal component powder comprises a pre-alloyed gas-atomized powder according to the aforementioned general formula or a mixed powder of elements formulated according to the chemical element composition in the general formula.

[0054] Furthermore, the multi-principal element powder is a mixed powder obtained by mechanically mixing elemental powders prepared according to the chemical element composition, and the elemental powders are placed in a planetary ball mill and mixed for 1 to 5 hours.

[0055] In some preferred embodiments, the multi-principal component powder is spherical or near-spherical powder with a particle size range of 15–53 μm.

[0056] In some preferred embodiments, the oxygen content of the multi-principal component powder is ≤0.10 wt.%.

[0057] In some preferred embodiments, the material of the substrate includes stainless steel and / or high-strength steel, but is not limited thereto.

[0058] In some preferred embodiments, the preparation method specifically includes:

[0059] The multi-principal component powder is dried under vacuum or inert gas protection; the drying temperature is 100-200 ℃ and the time is 1-3 h.

[0060] The substrate is preheated to a surface temperature of 300–380 °C.

[0061] The multi-principal element powder is clad onto the surface of a preheated substrate to form a coating using laser cladding technology. The process parameters used in the laser cladding technology include: laser power of 350-600 W, scanning speed of 6-20 mm / s, overlap rate of adjacent passes of 45-60%, powder feeding speed of 6-12 r / min, and protective gas flow rate of 10-15 L / min.

[0062] Furthermore, after the cladding is completed, the heating system is turned off, allowing the coating to cool naturally in the air, thus obtaining a wear-resistant coating of a eutectic high-entropy alloy with a micro-nano hierarchical heterostructure.

[0063] In some preferred embodiments, the linear energy density during the laser cladding deposition process is 25–90 J / mm.

[0064] In some more specific embodiments, the method for preparing the wear-resistant coating of the micro / nano hierarchical heterostructure eutectic high-entropy alloy includes:

[0065] S1: Vacuum or inert gas protection drying treatment is performed on multi-principal element alloy powder. The drying temperature is 100-200℃ and the time is 1-3 h.

[0066] S2: Preheat the workpiece substrate to bring the surface temperature of the substrate to 300-380 ℃;

[0067] S3: A coating is formed on the surface of the substrate preheated in step S2 using laser cladding process. The process parameters for laser cladding are controlled as follows: laser power 350-600 W, scanning speed 6-20 mm / s, overlap rate of adjacent passes 45-60%, powder feeding speed 6-12 r / min, and protective gas flow rate 10-15 L / min.

[0068] S4: After the cladding is completed, the heating system is turned off, and the resulting coating is allowed to cool naturally in the air to form the above-mentioned micro-nano multi-level heterostructure eutectic high-entropy alloy wear-resistant coating.

[0069] Preferably, the multi-principal alloy powder in step S1 is a pre-alloyed gas-atomized powder composed of the aforementioned chemical elements, or a composite powder obtained by mechanically mixing elemental powders prepared according to the aforementioned chemical element composition, and the oxygen content of the powder is not higher than 0.10 wt.%; the powder is preferably spherical or near-spherical powder, and the particle size range is preferably 15 to 53 μm.

[0070] Preferably, when using mechanical mixing of elemental powders, each elemental powder should be placed in a planetary ball mill and mixed for 1 to 5 hours to ensure uniform mixing.

[0071] Preferably, the workpiece substrate in step S2 is stainless steel or high-strength steel. Preheating the substrate helps reduce thermal stress during the cladding process and improves the forming quality.

[0072] Another aspect of this invention provides the application of the aforementioned micro / nano hierarchical heterostructure eutectic high-entropy alloy wear-resistant coating in the surface protection of key components of marine equipment.

[0073] In some preferred embodiments, the application includes the use of the eutectic high-entropy alloy wear-resistant coating in the protection of critical components of marine equipment against atmospheric salt spray corrosion, seawater corrosion, wear, or wear-corrosion coupled damage.

[0074] In some preferred embodiments, the key components of the marine equipment include friction parts, mating parts, sealing parts, or connecting parts in air and sea equipment, marine equipment, and underwater marine equipment.

[0075] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. This embodiment is implemented on the premise of the technical solution of the invention, and provides detailed implementation methods and specific operation processes. However, the protection scope of the present invention is not limited to the following embodiments.

[0076] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.

[0077] This invention is based on Al-Co-Cr-Fe-Ni-Ti-Nb eutectic high-entropy alloys. By controlling the content of Al, Ti and Nb elements and their sum, i.e., controlling the range of values ​​of a+f+g, the effects of these elements on the coating microstructure, phase composition, nanoscale compositional modulation structure formation and wear resistance are investigated.

[0078] Examples 1-4 all meet the chemical composition range defined by this invention, illustrating that the target micro / nano hierarchical heterostructure can be formed within the composition window of this invention, and superior corrosion resistance and abrasion resistance can be obtained. Comparative Examples 1-3 are used to illustrate that when the total amount of the key elements is lower or higher than the range defined by this invention, or when Ti and Nb elements are missing, the coating is difficult to form the target structure or its comprehensive performance is significantly reduced, thus more clearly reflecting the technical effect of the composition range and micro / nano hierarchical heterostructure design of this invention. Comparative Examples 4-6 are from patent documents CN120608236A, CN117821864A, and CN120158743A, which disclose the corrosion or abrasion resistance of high-entropy alloys.

[0079] Example 1

[0080] This embodiment provides a wear-resistant coating of a micro / nano hierarchical heterostructure eutectic high-entropy alloy and its preparation method, which is obtained through the following steps:

[0081] S1: Al, Co, Cr, Fe, Ni, Ti, and Nb elemental powders were weighed according to the atomic percentages: Al=15.4 at.%, Co=15.4 at.%, Cr=15.4 at.%, Fe=16.4 at.%, Ni=32.9 at.%, Ti=3.5 at.%, and Nb=1.0 at.%. The powder particle size range was 15~53 μm. The weighed powder was placed in a planetary ball mill with a material-to-ball ratio of 1:15 and a milling time of 2 h. Subsequently, the alloy powder was dried in a vacuum drying oven at 150 ℃ for 1.5 h to obtain eutectic high-entropy alloy powder.

[0082] S2: First, the surface oxide layer of the substrate is removed by grinding. Then, the surface of the 0C16NiMo stainless steel substrate is cleaned with acetone and anhydrous ethanol respectively. Then, the substrate is placed on a constant temperature heating platform for preheating treatment. The preheating temperature is 360 ℃ and the preheating time is >1 h, so that the surface temperature of the substrate reaches 360 ℃.

[0083] S3: A coating is prepared on the surface of a preheated substrate using a circular beam laser cladding process. The process parameters are set as follows: laser power 500 W, scanning speed 10 m / s, overlap rate 50%, powder feeding speed 8 r / min, and protective gas flow rate 15 L / min.

[0084] S4: After the cladding is completed, turn off the heating system and allow the resulting coating to cool naturally in the air.

[0085] This embodiment illustrates that when the total amount of Al and Ti elements is within the limits defined by this invention and an appropriate amount of Nb is introduced, the prepared coating maintains the target micro / nano hierarchical heterostructure while exhibiting excellent corrosion and abrasion resistance.

[0086] Example 2

[0087] This embodiment provides a wear-resistant coating of a micro / nano hierarchical heterostructure eutectic high-entropy alloy and its preparation method. The difference between this embodiment and Example 1 is that Al, Co, Cr, Fe, Ni, and Ti elemental powders are prepared according to the atomic percentages: Al = 15.9 at.%, Co = 15.9 at.%, Cr = 15.9 at.%, Fe = 16.9 at.%, Ni = 33.4 at.%, Ti = 3.0 at.%, and Nb = 0 at.%. The preparation steps are the same as in Example 1.

[0088] This embodiment illustrates that, under Nb-free conditions, when the total amount of Al and Ti elements is within the limits defined by this invention, the prepared coating can still form a micron-scale FCC / BCC biphase heterostructure and a nanoscale composition modulation structure within the BCC phase domain.

[0089] Example 3

[0090] This embodiment provides a wear-resistant coating of a micro / nano-level heterostructure eutectic high-entropy alloy and its preparation method. The difference from Example 1 is that Al, Co, Cr, Fe, Ni, and Ti elemental powders are prepared according to the atomic percentages: Al = 15.3 at.%, Co = 15.3 at.%, Cr = 15.3 at.%, Fe = 16.3 at.%, Ni = 32.8 at.%, Ti = 5.0 at.%, and Nb = 0 at.%. The preparation steps are the same as in Example 1.

[0091] This embodiment illustrates that, under Nb-free conditions, when the Ti content is close to the upper limit specified in this invention, the prepared coating can still maintain the target biphase structure and nanoscale heterostructure, thus supporting the upper range of the composition range of this invention.

[0092] Example 4

[0093] This embodiment provides a wear-resistant coating of a micro / nano-level heterostructure eutectic high-entropy alloy and its preparation method. The difference between this embodiment and Example 1 is that Al, Co, Cr, Fe, Ni, Ti, and Nb elemental powders are prepared according to the atomic percentages: Al = 15.1 at.%, Co = 15.1 at.%, Cr = 15.1 at.%, Fe = 16.1 at.%, Ni = 32.6 at.%, Ti = 4.0 at.%, and Nb = 2 at.%. The preparation steps are the same as in Example 1.

[0094] This embodiment illustrates that when the Nb content is close to the upper limit specified in this invention, the prepared coating can still form the micro-nano hierarchical heterostructure described in this invention, thereby supporting the upper limit of the Nb content specified in this invention.

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 1 is that it uses conventional AlCoCrFeNi. 2.1 The coating was prepared using a eutectic high-entropy alloy system, with the elements in atomic percentage as follows: Al = 16.4 at.%, Co = 16.4 at.%, Cr = 16.4 at.%, Fe = 16.4 at.%, Ni = 34.4 at.%, Ti = 0 at.%, Nb = 0 at.%. The preparation steps were the same as in Example 1.

[0097] Comparative Example 2

[0098] The comparative example differs from Example 1 in that: Al = 12.0 at.%, Ti = 2.0 at.%, Nb = 0 at.%, and the content of other elements is supplemented according to the design, with the total content meeting 100 at.%, and a+f+g = 14 at.%. Its preparation steps are the same as those in Example 1.

[0099] This comparative example illustrates that when the total amount of Al, Ti, and Nb elements is below the lower limit specified in this invention, the resulting coating, as characterized by SEM, deviates from the stable biphase eutectic structure required by this invention, and the eutectic structure is destroyed, which is not conducive to obtaining the target structure with both corrosion resistance and wear resistance as described in this invention.

[0100] Comparative Example 3

[0101] The comparative example differs from Example 1 in that: Al = 16.0 at.%, Ti = 5.0 at.%, Nb = 2 at.%, and the content of other elements is supplemented according to the design, with the total content meeting 100 at.%, and a+f+g = 23.5 at.%. Its preparation steps are the same as those in Example 1.

[0102] This comparative example illustrates that when the total amount of Al, Ti, and Nb elements exceeds the upper limit specified in this invention, the resulting coating, as characterized by XRD and SEM, deviates from the stable biphase eutectic structure required by this invention. The biphase volume fraction changes significantly, and the coating exhibits obvious cracking, resulting in a significant reduction in forming quality. This is not conducive to obtaining the target structure with both corrosion resistance and wear resistance as described in this invention.

[0103] Comparative Example 4

[0104] This comparative example is from patent document CN120608236A, which discloses a high-strength, corrosion-resistant Ni-Fe-Co-Cr-Al-Cu near-eutectic high-entropy alloy and its preparation method, comprising Ni 36 Fe 16 Co 16 Cr 16 Al 13 Cu3-treated state (Al13Cu3) and Ni 36 Fe 16 Co 16 Cr 16 Al 10 Two examples of Cu6-treated state (Al10Cu6).

[0105] Comparative Example 5

[0106] This comparative example is from patent document CN117821864A, which discloses a method for improving the corrosion resistance of eutectic high-entropy alloys, comprising AlCrFe 1.5 Ni 2.6As-cast (cast state) and AlCrFe 1.5 Ni 2.6 Two examples of the heat-treated state (heat-treated state).

[0107] Comparative Example 6

[0108] This comparative example is from patent document CN120158743A, which discloses a method for preparing a high-entropy alloy coating resistant to seawater abrasion and corrosion, comprising annealing FeCrCoMnSi at 600℃. 0.6 Coating - Pre-coated layer width 7 mm (Si) 0.6 -7) Annealed FeCrCoMnSi at 600℃ 0.6 Coating - Pre-coated layer width 10 mm (Si) 0.6 -10), 600℃ annealed FeCrCoMnSi 0.6 Coating - Pre-fabrication layer width 15 mm (Si) 0.6 -15), 600℃ annealed FeCrCoMnSi 0.6 Coating - Pre-fabrication layer width 20 mm (Si) 0.6 -20) Four implementation examples.

[0109] The structural characteristics and corrosion resistance test data of the preferred embodiments 1-4 and comparative embodiments 1-6 of this invention are shown in Table 1. As can be seen from the data in Table 1, the novel eutectic high-entropy alloy wear-resistant cladding coatings prepared in embodiments 1-4 can stably form a micron-scale dual-phase heterostructure composed of a continuous FCC phase and a BCC phase domain. Furthermore, a nanoscale compositional modulation structure composed of a disordered BCC phase and an ordered B2 phase is formed within the BCC phase domain, thereby constructing a micro / nano hierarchical heterostructure. The self-corrosion current density of the coating in simulated seawater (3.5 wt.% NaCl solution) environment is all above 10. -8 A / cm -2 The order of magnitude, the passivation current density is all in the range of 10 -7 A / cm -2 The magnitudes are all greater than 660 mV, and the pitting potentials are all greater than 660 mV.

[0110] Comparative Example 1 uses conventional AlCoCrFeNi 2.1 As a control, the eutectic high-entropy alloy system lacks the micro / nano-level heterostructure induced by compositional design described in this invention. In particular, it is difficult to form a nanoscale BCC / B2 compositional modulation structure comparable to that of the embodiments of this invention within the BCC phase domain, resulting in its self-corrosion current density being only 10. -6 A / cm -2The coating size is two orders of magnitude lower than that provided in the embodiments of the present invention, and its pitting potential is 296 mV, which is far lower than the pitting resistance level of the coating provided in the preferred embodiments of the present application. Although the coating obtained in Comparative Example 2 can still form a certain multiphase structure, its hypoeutectic structure deviates significantly from the target structure required by the present invention, the degree of structure refinement is reduced, and the multi-scale heterostructure characteristics are not obvious, resulting in a significant increase in its self-corrosion current density, narrowing of the passivation range and reduction of pitting potential, indicating that its corrosion resistance is inferior to that of the embodiments of the present invention. In Comparative Example 3, because a+f+g is higher than the upper limit of the present invention, the coating structure deviates from the stable biphase eutectic and nanoscale heterostructure required by the present invention, resulting in coating cracking and inaccurate electrochemical data measurement, which is not conducive to balancing corrosion resistance and wear resistance, indicating that the upper limit of the present invention is reasonable. Although the self-corrosion current density of the near-eutectic high-entropy alloy prepared in Comparative Example 4 reaches 10 -8 A / cm -2 The magnitude is still lower than the self-corrosion current density of the coating provided in this application; the lowest self-corrosion current density and passivation current density of the AlCoCrFeNi eutectic high-entropy alloy improved by heat treatment in Comparative Example 5 both reached 10. -7 A / cm -2 The magnitude of the corrosion current is on the order of magnitude, but the maximum pitting potential is only 254 mV (converted from 210 mV relative to a saturated calomel electrode to a relative silver / silver chloride electrode), significantly lower than that of the coatings in Examples 1-4. Furthermore, the high-entropy alloy coating involved in Comparative Example 6 has a multiphase structure including FCC+BCC+silicides, and even after stress-relief annealing, the self-corrosion current density of the coating in a simulated seawater environment remains high, at 10... -6 A / cm -2 The magnitude is significant. This demonstrates that the micro / nano hierarchical heterostructure eutectic high-entropy alloy coating provided in this application exhibits significant advantages in corrosion resistance in simulated seawater environments.

[0111] Table 1. Microstructure and electrochemical corrosion data of samples obtained in Examples 1-4 and Comparative Examples 1-6

[0112]

[0113] The abrasion performance test data of Examples 1-4 and Comparative Examples 1-6 are shown in Table 2. As can be seen from the data in Table 2, the volumetric wear rate of the novel micro / nano hierarchical heterostructure eutectic high-entropy alloy cladding coatings prepared in Examples 1-4 is less than 3 × 10⁻⁶ under simulated seawater conditions. -6 mm 3 / N·m, the coating exhibits excellent wear resistance; in contrast, the traditional eutectic high-entropy alloy in Comparative Example 1 and the multiphase multi-principal element alloy coating in Comparative Example 6 only achieved a wear rate of 10% in simulated seawater environment. -5 mm 3The N·m level is evident. This demonstrates that the micro / nano hierarchical heterostructure eutectic high-entropy alloy coating provided in this application exhibits significant advantages in simulating seawater abrasion resistance.

[0114] Table 2. Volumetric wear rate data of the coatings prepared in Examples 1-4 and Comparative Examples 1-6 under simulated seawater environment.

[0115]

[0116] The wear-resistant coatings of micro / nano hierarchical heterostructure eutectic high-entropy alloys prepared in Examples 1-4 and Comparative Examples 1-3 were characterized and tested as follows:

[0117] (1) Scanning electron microscope image:

[0118] The microstructure characteristics of the coating were observed using a FE-SEM Gemini SEM 300 scanning electron microscope (SEM).

[0119] (2) XRD test:

[0120] Phase structure analysis of the coating was performed using an XRD diffractometer, with radial scanning at scattering angles of 2θ from 10° to 100° and a scanning step of 0.02°.

[0121] (3) XPS test:

[0122] The elemental composition of the passivation film on the coating surface was analyzed using X-ray photoelectron spectroscopy (XPS, AXIS SUPRA+), and the passivation film was obtained by constant potential polarization.

[0123] (4) Corrosion resistance test:

[0124] The corrosion resistance test was conducted at room temperature using a Gamry electrochemical workstation with a three-electrode system. The polished samples from Examples 1-4 and Comparative Examples 1-2 were used as the working electrode, silver / silver chloride (Ag / AgCl) was used as the reference electrode, and platinum (Pt) sheet was used as the counter electrode. The corrosion solution was simulated artificial seawater (3.5 wt.% NaCl solution).

[0125] (5) Microhardness test:

[0126] The coating surface was tested using a micro Vickers hardness tester according to conventional microhardness testing methods for metallic materials. After grinding and polishing the sample, multiple measurements were taken at various points in the central region of the coating surface. The test load was 300 g, and the holding time was 15 s. Five points were tested for each sample, and the average value was taken as the microhardness result.

[0127] (6) Seawater environment erosion performance test:

[0128] The abrasion performance was tested at room temperature using an in-situ friction-corrosion testing machine with a load of 10 N, a friction frequency of 1 Hz, a friction time of 0.5 h, and a corrosion solution of simulated artificial seawater (3.5 wt.% NaCl solution). The wear volume of the wear track area was measured using a three-dimensional confocal microscope, and the volumetric wear rate of the sample was calculated by dividing the wear volume by (load × total stroke).

[0129] (7) Transmission electron microscopy images and elemental surface distribution analysis:

[0130] The microstructure and elemental distribution characteristics of the coating, as well as the passivation film and cross-sectional microstructure characteristics of the coating after wear in a simulated seawater environment, were observed using a ThemoFisher Talos F200x transmission electron microscope.

[0131] Test results description:

[0132] The XRD patterns of the coatings obtained in Examples 1-2 and Comparative Examples 1-2 all exhibited a two-phase diffraction characteristic dominated by the FCC phase and the BCC / B2 phase. Specifically, weak diffraction peaks appeared at the (100) crystal plane in Examples 1 and 2, indicating the presence of an ordered B2 phase in the coating. Compared to Comparative Example 1, the intensity of the BCC / B2 related diffraction peaks was enhanced, indicating that the composition design was beneficial in introducing an ordered structure while maintaining the two-phase microstructure. In particular, the BCC / B2 related diffraction peaks in Comparative Example 2 were further enhanced, indicating that excessive alloying elements could easily lead to an enhancement of the hard phase characteristics in the microstructure, resulting in cracking of the coating.

[0133] Figure 1 The image shows a low-magnification TEM image of the wear-resistant coating of the micro / nano hierarchical heterostructure eutectic high-entropy alloy prepared in Example 1. The SEM image and TEM test results of the coating prepared in Example 1 show that the coating consists of a continuously distributed FCC phase and BCC phase domains filled within the network structure, exhibiting obvious micron-scale dual-phase heterostructure characteristics. The low-magnification TEM image and SAED show that amplitude-modulated decomposition structures and ordered phase precipitation exist within the BCC phase domains, forming nanoscale composition modulation regions. This indicates that under rapid solidification and synergistic compositional regulation, a nanoscale heterostructure modulation structure is formed within the coating, where disordered BCC phases and ordered B2 phases coexist or are coupled, thus proving the micro / nano hierarchical heterostructure characteristics described in this invention.

[0134] Figure 2To demonstrate the regular distribution characteristics of the main elements within the BCC phase domain of the coating in Example 1 at the micro-nano scale, corrosion-resistant elements such as Cr achieve a relatively favorable distribution state at the nanoscale, which helps to improve the continuity and stability of the passivation film formation on the coating surface; while the local enrichment or coordinated distribution of elements such as Al and Ti is beneficial to improving the stability of the film composition and enhancing the regeneration ability after film damage. This illustrates that the present invention achieves the coupling of micron-scale dual-phase partitioning and nanoscale composition modulation through the synergistic effect of composition design and rapid solidification process.

[0135] Figure 3 The figures show the potentiodynamic polarization test results of the coatings prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2. As can be seen from the figures, compared with Comparative Example 1 and Comparative Example 3, Examples 1 and 2 both exhibit superior electrochemical response characteristics, with a self-corrosion current density reaching 10. -8 A / cm -2 The order of magnitude, with a passivation current density of 10 -7 A / cm -2 The magnitude of the pitting potential is higher than 650 mV, indicating that the limited composition and structural design of this invention can effectively improve the passivation film stability and corrosion resistance of the coating in a simulated seawater environment.

[0136] Figures 4a-4c The images show cross-sectional TEM images, STEM-EDS surface scans, and XPS measurements of the passivation film on the surface of the micro / nano hierarchical heterostructure eutectic high-entropy alloy wear-resistant coating prepared in Example 1. As can be seen from the figures, continuous, dense, and well-bonded passivation films can be formed on the surfaces of different phases in the coating of Example 1. The passivation films contain multi-component oxides such as Cr, Al, Ti, Nb, Co, Fe, and Ni, which is beneficial for the coating to effectively resist the Cl environment of seawater. - erosion.

[0137] Figure 5 The results show the microhardness test results for Examples 1, 2, Comparative Examples 1, and 2. The results indicate that the coatings obtained in Examples 1 and 2 have higher hardness values ​​compared to Comparative Examples 1 and 2, demonstrating that the micro / nano hierarchical heterostructure constructed by the present invention through specific component design and a non-equilibrium rapid solidification manufacturing process is beneficial for improving the coating's resistance to localized plastic deformation.

[0138] Figures 6a-6b These are schematic diagrams of the average two-dimensional profile of the wear track cross-section and the three-dimensional morphology of the surface after the abrasion test of the coating prepared in Example 1 in an artificial seawater environment. Figures 6c-6d These are schematic diagrams of the average two-dimensional profile of the wear track cross-section and the three-dimensional morphology of the surface after the abrasion test of the coating prepared in Example 2 in an artificial seawater environment. Figures 6e-6fThe figures show the average two-dimensional profile of the wear track cross-section and the three-dimensional morphology of the surface after abrasion testing of the coating prepared in Comparative Example 1 in an artificial seawater environment. As can be seen from the figures, the wear tracks after abrasion in Examples 1 and 2 are shallower and the wear volume is smaller; the wear track in Comparative Example 1 is deeper, indicating that the traditional eutectic high-entropy alloy system is more prone to surface damage and material removal under the coupled action of simulated seawater environment and mechanical friction, making it difficult to simultaneously achieve corrosion resistance and wear resistance. In contrast, Examples 1 and 2, by forming a micro-nano hierarchical heterostructure, improve the substrate load-bearing capacity, surface shear damage resistance, and rapid repair capability after surface film damage, thus significantly reducing synergistic damage during abrasion, indicating superior wear resistance under simulated seawater environment. The volumetric wear rate data of the coatings prepared in Examples 1-2 and Comparative Example 1 under simulated seawater environment are listed in Table 2.

[0139] Figure 7 This is a TEM image of the near-surface cross-section region of the wear-resistant coating of the micro / nano hierarchical heterostructure eutectic high-entropy alloy prepared in Example 1 after a simulated seawater abrasion test. Figure 7 It can be seen that after undergoing simulated seawater abrasion, the near-surface region of the coating in Example 1 still maintains good structural integrity, with only limited structural response or deformation adjustment occurring locally on the surface. No severe penetrating damage or large-scale instability was observed. This indicates that the micron-scale biphase heterogeneous structure and nanoscale ordered / disordered modulation structure in Example 1 have strong surface damage resistance in abrasive environments. On the one hand, the multi-level heterogeneous interface can disperse local stress and inhibit crack initiation and propagation. On the other hand, even if local film damage occurs near the surface under the coupling of friction and corrosion, it can achieve rapid repassivation due to its superior compositional distribution and structural basis, thereby reducing the extension of damage to deeper regions. As a result, it can still maintain high structural stability in actual abrasive environments, which is an important reason for its excellent abrasion resistance.

[0140] Figure 8 The image shows a SEM image of the coating prepared in Comparative Example 2. As can be seen from the image, when the total amount of Al, Ti, or Nb elements is below the lower limit specified in this invention, the resulting coating is difficult to form the refined and stable micro / nano-level heterostructure required by this invention. This is manifested in indistinct microstructure modulation, coarsening of local phase regions, and insufficient overall microstructure uniformity. This indicates that when the composition is insufficiently controlled, it is difficult to establish a stable nanoscale heterostructure modulation basis during rapid solidification, and the wear-resistant coating of the micro / nano-level heterostructure eutectic high-entropy alloy provided by this invention cannot be prepared.

[0141] Figure 9SEM images of the coating prepared in Comparative Example 3 are shown. Because Al+Ti+Nb exceeds the upper limit specified in this invention, the coating microstructure deviates from the stable biphase eutectic and nanoscale heterostructure required by this invention, leading to an imbalance in the rapidly solidified microstructure. The increased proportion of hard and brittle phases causes significant cracking in the coating, significantly reducing its forming quality.

[0142] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0143] It should be understood that the technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made to the technical solutions of the present invention without departing from the spirit and scope of the claims are within the scope of protection of the present invention.

Claims

1. A wear-resistant coating for a micro / nano hierarchical heterostructure eutectic high-entropy alloy, characterized in that, The general formula for the chemical element composition of the eutectic high-entropy alloy wear-resistant coating is Al. a Co b Cr c Fe d Ni e Ti f Nb g , among them, a=13~17 at.%, b=14~17 at.%, c=14~17 at.%, d=16~19 at.%, e=30~34 at.%, f=3~5 at.%, g=0~3 at.%, a+f+g=16~22 at.%, a+b+c+d+e+f+g=100 at.%; The eutectic high-entropy alloy wear-resistant coating includes an FCC phase and a BCC phase domain. The BCC phase domain is distributed within the FCC phase, which serves as the matrix. A nanoscale composition modulation region is formed within the BCC phase domain. The nanoscale composition modulation region is composed of a disordered BCC phase and an ordered B2 phase. The eutectic high-entropy alloy wear-resistant coating has a micron-scale FCC / BCC dual-phase heterostructure and a nanoscale BCC / B2 heterostructure. In the nanoscale component modulation region, the disordered BCC phase and the ordered B2 phase are distributed in a continuous, interwoven maze-like pattern, and the modulation period of the disordered BCC phase and the ordered B2 phase is 20 nm to 200 nm; furthermore, the passivation film formed by the eutectic high-entropy alloy wear-resistant coating has the ability to be repassivated after local film rupture.

2. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The nanoscale component modulation region is formed by amplitude modulation decomposition.

3. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The interface between the disordered BCC phase and the ordered B2 phase in the nanoscale composition modulation region is coherent.

4. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The volume fraction of the FCC phase in the eutectic high-entropy alloy wear-resistant coating is 40% to 55%.

5. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The thickness of the eutectic high-entropy alloy wear-resistant coating is 0.5~1.5 mm.

6. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The eutectic high-entropy alloy wear-resistant coating is an Al-Co-Cr-Fe-Ni-Ti-Nb system coating formed using non-equilibrium rapid solidification technology.

7. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The eutectic high-entropy alloy wear-resistant coating forms a continuous passivation film on its surface in a simulated seawater environment. The passivation film contains oxides of Cr, Al, Ti, Nb, Co, Fe, and Ni.

8. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The eutectic high-entropy alloy wear-resistant coating exhibits a self-corrosion current density ≤ 8.53 × 10⁻⁶ under simulated seawater conditions. -8 A / cm -2 The passivation current density is ≤8.67×10⁻⁶. -7 A / cm -2 Its pitting potential relative to the silver / silver chloride electrode is ≥660 mV.

9. The eutectic high-entropy alloy wear-resistant coating according to claim 1, characterized in that: The eutectic high-entropy alloy wear-resistant coating exhibits a volumetric wear rate ≤3×10⁻⁶ under simulated seawater conditions. -6 mm 3 / (N·m).

10. The method for preparing a wear-resistant coating of a micro / nano hierarchical heterostructure eutectic high-entropy alloy as described in any one of claims 1-9, characterized in that, include: Provides substrates and multi-principal component powders; Furthermore, the multi-principal element powder is clad onto the surface of a substrate using laser cladding technology, and then naturally cooled in air to obtain a wear-resistant coating of a eutectic high-entropy alloy with a micro-nano multi-level heterostructure.

11. The preparation method according to claim 10, characterized in that: The multi-principal-element powder includes pre-alloyed gas-atomized powder according to the general formula or a mixture of single-element powders formulated according to the chemical element composition in the general formula.

12. The preparation method according to claim 10, characterized in that: The multi-principal component powder is spherical or near-spherical, with a particle size range of 15–53 μm.

13. The preparation method according to claim 10, characterized in that: The oxygen content of the multi-principal component powder is ≤0.10 wt.%.

14. The preparation method according to claim 10, characterized in that: The substrate material includes stainless steel and / or high-strength steel.

15. The preparation method according to claim 10, characterized in that, Specifically, it includes: The multi-principal component powder is dried under vacuum or inert gas protection; the drying temperature is 100-200℃ and the time is 1-3 h. The substrate is preheated to a surface temperature of 300–380 °C. The multi-principal element powder is clad onto the surface of a preheated substrate to form a coating using laser cladding technology. The process parameters used in the laser cladding technology include: laser power of 350-600 W, scanning speed of 6-20 mm / s, overlap rate of adjacent passes of 45-60%, powder feeding speed of 6-12 r / min, and protective gas flow rate of 10-15 L / min. Furthermore, after the cladding is completed, the heating system is turned off, allowing the coating to cool naturally in the air, thus obtaining a wear-resistant coating of a eutectic high-entropy alloy with a micro-nano hierarchical heterostructure.

16. The preparation method according to claim 10, characterized in that: The linear energy density during the laser cladding deposition process is 25–90 J / mm.

17. The application of the wear-resistant coating of the eutectic high-entropy alloy with micro-nano hierarchical heterostructure as described in any one of claims 1-9 in the surface protection of key components of marine equipment.

18. The application according to claim 17, characterized in that: The applications include the use of the eutectic high-entropy alloy wear-resistant coating in the protection of key components of marine equipment against atmospheric salt spray corrosion, seawater corrosion, wear, or wear-corrosion coupled damage.

19. The application according to claim 17, characterized in that: The key components of marine equipment include friction parts, mating parts, sealing parts, or connecting parts in air and sea equipment, marine equipment, and underwater equipment.

Citation Information

Patent Citations

  • Method for improving corrosion resistance of eutectic high-entropy alloy

    CN117821864A

  • Preparation method of seawater wear and corrosion resistant high-entropy alloy coating

    CN120158743A

  • High-strength corrosion-resistant Ni-Fe-Co-Cr-Al-Cu series near-eutectic high-entropy alloy and preparation method thereof

    CN120608236A